The association between eosinophils (CD16+ eosinophils), basophils (CD203+ basophils), and CD23 B lymphocytes in patients with atopic dermatitis on dupilumab therapy: pilot study - Čelakovská, Jarmila; Čermáková, Eva; Boudková, Petra; Andrýs, Ctirad; Krejsek, Jan (Dermatology and therapy, 2023)
BACKGROUND: Eosinophils, basophils, and the molecule CD23 on B cells are involved in the pathophysiology of atopic dermatitis (AD). The molecule CD23 is involved in the regulation of IgE synthesis and is expressed by activated B cells. The molecule CD16 is used to assess the activation of eosinophils and CD203 of basophils. The association between the count of eosinophils, basophils, CD16+ eosinophils, CD203+ basophils and the expression of the activation marker CD23 on B cells in patients with AD (with and without dupilumab therapy) is not described. OBJECTIVE: The aim of this pilot study is to evaluate the association between the blood count of eosinophils, basophils, relative CD16+ eosinophils, relative CD203+ basophils, and the expression of molecule CD23 on B cells and on their subsets (total, memory, naive, switched, non-switched) in patients suffering from AD (with and without dupilumab therapy) and in control group. METHODS: A total of 45 patients suffering from AD were examined; 32 patients without dupilumab treatment (10 men, 22 women, average age 35 years), 13 patients with dupilumab treatment (7 men, 6 women, average age 43.4 years), and 30 subjects as a control group (10 men, 20 women, average age 44.7 years). Immunophenotype was examined by flow cytometry in which monoclonal antibodies with fluorescent molecules were used. For statistical analysis we used non-parametric Kruskal-Wallis one-factor analysis of variance with post hoc by Dunn's test with Bonferroni modification and the Spearman's rank correlation coefficient; for coefficients higher than 0.41, we report R2 (percent of variation explained). RESULTS: The absolute count of eosinophils was significantly higher in patients with AD (with and without dupilumab) in comparison to healthy subjects. The difference in the relative count of CD16+ eosinophils in patients with AD (with and without dupilumab therapy) compared with control is not statistically significant. In patients with dupilumab therapy the significantly lower count of relative CD203+ basophils was confirmed compared with control. The higher association between the count of eosinophils (absolute and relative) and the expression of CD23 marker on B cells was confirmed in patients with dupilumab therapy; in contrast, this association was low in patients with AD without dupilumab therapy and in healthy subjects. CONCLUSION: The higher association between the count of eosinophils (absolute and relative) and the expression of CD23 marker on B cells was confirmed in patients with AD under dupilumab therapy. It suggests that IL-4 production by eosinophils may play a role in B lymphocyte activation. The significantly lower count of CD203+ basophils has been demonstrated in patients with dupilumab therapy. This reduction of CD203+ basophil count may contribute to the therapeutic effects of dupilumab by reducing the inflammatory response and allergic reactions in patients with AD.
Keywords: Basophils; Expression of CD23 on B cells; Activation markers CD16; Atopic dermatitis patients; Eosinophils; Dupilumab therapy; CD203